Reactive Oxygen Species in Pathogen Clearance: The Killing Mechanisms, the Adaption Response, and the Side Effects - Li, Hao; Zhou, Xuedong; Huang, Yuyao; Liao, Binyou; Cheng, Lei; Ren, Biao (Frontiers in Microbiology, 2021)
Reactive oxygen species (ROS) are thought to play important role in both antibiotic-mediated killing and host-mediated killing. However, the involvement of ROS in antibiotic-mediated killing and complexities in host environments challenges the paradigm. In the case of bacterial pathogens, the examples of some certain pathogens thriving under ROS conditions prompt us to focus on the adaption mechanism that pathogens evolve to cope with ROS. Based on these, we here summarize the exact mechanisms of ROS-mediated killing of either antibiotics or the host, the examples of bacterial adaption that successful pathogens have evolved to defend or thrive under ROS conditions, and the side effects of ROS in pathogen clearance.